Modeling and Simulation of Piezoelectric Cantilever Beam Energy Harvester - Sami A. Mostafa, Ayman M. Brisha (International Journal of Advanced Science and Technology, 2020)
Piezoelectric energy harvesting is one of the green power collecting methods. The harvester may consist of either a cantilever beam or a plate. In the present paper, a model of a cantilever of a thin layer of piezoelectric material bonded hardly to an aluminum beam is used as a piezoelectric power harvester. The suggested model will suffer from an external mechanical vibrating force. Three power methods, the known method Euler Bernoulli, pin-force, and enhanced pin-force are applied on the model and resulting electric powers are estimated and compared. An analytical study concerning the beam and the piezoelectric parameters, such as the length and the thickness, is carried out. The study is done to save time spent in multiple experiments and also seeking for more efficient and practical model. Matlab algorithms are designed to carry out the analytical study and plotting the output results. The maximum power is calculated applying each of the three force methods. The power harvested from the beam model reaches about 870 micro watts which is quit sufficient to derive many electronic devices such as microprocessors. Key words: Power harvesting, Piezoelectric harvester, vibration to electric power conversion, piezoelectric cantilever beam model.